Contrasting Binding of Fisetin and daidzein in γ-Cyclodextrin Nanocavity - Pahari, Biswapathik (2012)
Steady state and time resolved fluorescence along with anisotropy and induced circular dichroism (ICD) spectroscopy provide useful tools to observe and understand the behavior of the therapeutically important plant flavonoids fisetin and daidzein in γ-cyclodextrin (γ-CDx) nanocavity. Benesi-Hildebrand plots indicated 1:1 stoichiometry for both the supramolecular complexes. However the mode of the binding of fisetin significantly differs from daidzein in γ-CDx, as is observed from ICD spectra which is further confirmed by docking studies. The interaction with γ-CDx proceeds mainly by the phenyl rings and partly by the chromone ring of fisetin whereas only the phenyl rings takes part for daidzein. A linear increase in the aqueous solubility of the flavonoids is assessed from the increase in the binding of flavonoids with γ-CDx cavity, which are determined by gradual increase in the ICD signal, fluorescence emission as well as increase in fluorescence anisotropy with increasing [γ-CDx]. This confirms the γ-CDx as a nanovehicle for flavonoids fisetin and daidzein in improving their bioavailability.